2022
DOI: 10.3389/fmicb.2022.963917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term feeding with high fiber diets on growth, utilization of dietary fiber, and microbiota in pigs

Abstract: Finishing pigs can adapt to high-fiber diet smoothly according to the production performance and their intestinal microbiota through a 28-day trial or longer. However, it is unclear, at which stage during the experimental period, the adaptation occurred. Here we studied the dosage effects of dietary fiber (Total dietary fiber (TDF) from 16.70 to 24.11%) on growth performance, fiber digestibility, fecal microbiota, and microbial fermentation of finishing pigs during a 14-day feeding period. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…As shown in Figure S3e, Gram‐negative bacteria abundances were downregulated after salidroside treatment (68.94% to 48.97%, p = .0028), which might participate in the effect of salidroside on macrophage pyroptosis. Most species in Firmicutes were Gram‐positive bacteria and raised by salidroside, especially Lachnospiraceae and Ruminococcaceae, which have been reported to strengthen intestinal barrier via metabolism production (Keshteli et al, 2022; Pu et al, 2022). Actually, general decrease in dominant genera of Firmicute is a common feature of UC patients, such as Faecalibacterium and Roseburia, in which Faecalibacterium prausnitzii has been reported to induce specific Treg to maintain immunity homeostasis (Touch et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure S3e, Gram‐negative bacteria abundances were downregulated after salidroside treatment (68.94% to 48.97%, p = .0028), which might participate in the effect of salidroside on macrophage pyroptosis. Most species in Firmicutes were Gram‐positive bacteria and raised by salidroside, especially Lachnospiraceae and Ruminococcaceae, which have been reported to strengthen intestinal barrier via metabolism production (Keshteli et al, 2022; Pu et al, 2022). Actually, general decrease in dominant genera of Firmicute is a common feature of UC patients, such as Faecalibacterium and Roseburia, in which Faecalibacterium prausnitzii has been reported to induce specific Treg to maintain immunity homeostasis (Touch et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Pu et al also showed that as dietary fifiber increased, SCFAs production and microbial pyruvate metabolism and butanoate metabolism increased. Meanwhile, members of Prevotellaceae , Ruminococcaceae, and Lachnospiraceae have been linked to the fermentation of plant-derived non-starch polysaccharides to SCFAs [ 49 ]. As expected, a number of the predicted functions of these potential biomarkers in the H-AD of NDF and ADF were associated with microbial cell metabolism in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lignin, a high molecular weight polymer, cannot be broken down in the digestive tract [ 9 , 10 ]. Previous studies indicated that various microorganisms in the hindgut can ferment DF to produce a number of short-chain fatty acids (SCFAs), which not only promote the growth of beneficial microorganisms, but also improve the intestinal integrity and functions [ 11 , 12 ]. A diet rich in DF has also been found to reduce the risk of many dietary problems such as cardiovascular disease, type 2 diabetes, and Crohn’s disease in humans [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%